Determining the effective service life of silane treatments in concrete bridge decks. (30th July 2016) - Khanzadeh Moradllo, Mehdi; Sudbrink, Bryan; Ley, M. Tyler
Highlights: The effectiveness of silane is investigated in 60 bridge decks with service life of 6–20 years. The silane layer starts to decrease after 12 years of service. The average silane thickness is reduced by 75% in 17–20 year old bridges. Abrasion was not a significant silane deterioration mechanism in investigated structures. Silane deterioration starts in the bulk of the concrete and progresses towards the surface. Abstract: Silane is a commonly used surface treatment to reduce water entry into concrete. Only limited work has been done to show the effective lifespan of silane treatments. This work uses 360 cores taken from 60 bridge decks treated with silane that have been in-service between 6 and 20 years. Optical staining techniques showed that the average silane thickness started decreasing after 12 years of service. The deterioration primarily occurs from the bulk of the concrete towards the surface. This suggests that deterioration from the alkali pore solution of the concrete may be important.